The frequency, risk factors, and complications of gastrointestinal dysfunction during enteral nutrition in critically ill patients - Atasever AG; Ozcan PE; Kasali K; Abdullah T; Orhun G; Senturk E (Therapeutics and Clinical Risk Management, 2018)
Ayse Gulsah Atasever,1 Perihan Ergin Ozcan,2 Kamber Kasali,3 Taner Abdullah,4 Gunseli Orhun,2 Evren Senturk5 1Anesthesiology and Intensive Care, Sinop Ayancik State Hospital, Sinop, Turkey; 2Anesthesiology and Intensive Care, Istanbul University Hospital, Istanbul, Turkey; 3Biostatistics, Ataturk University, Erzurum, Turkey; 4Anesthesiology Department, Istanbul University Hospital, Istanbul, Turkey; 5Anesthesiology and Intensive Care, Koc University Hospital, Istanbul, Turkey Background: Gastrointestinal (GI) motility disorders in intensive care patients remain relatively unexplored. Nowadays, the frequency, risk factors and complications of GI dysfunction during enteral nutrition (EN) become more questionable. Aim: To evaluate the frequency, risk factors and complications of GI dysfunction during EN in the first 2 weeks of the intensive care unit (ICU) stay and to identify precautions to prevent the development of GI dysfunction and avoid complications.Methods: In this prospective observational study, we deliberately targeted at-risk patients. A total of 137 patients who received nasogastric tube feeding in an ICU of a tertiary hospital were enrolled.Results: The incidence of GI dysfunction that was found to be 63% which was associated mainly between MDR bacteria positivity and negative fluid balance. Diarrhea was observed in 36 patients (26%) and on 147 patient-days (incidence rate, 5.5 per 100 patient-days). The median day of diarrhea onset was 6 days after the initiation of EN. Forty patients (29%) presented with constipation (85% during the first week). Fifty patients (36%) exhibited upper digestive intolerance on 212 patient-days (incidence rate, 7.9 per 100 patient-days), after a median EN duration of 6 days (range, 2–14 days). Logistic regression analysis revealed MDR bacteria growth in the culture (OR, 1.75; 95% CI, 1.15–2.67; P=0.008) and negative fluid balance (OR, 0.57; 95% CI, 0.34–0.94; P=0.03) as the risk factors for GI dysfunction. We also showed that GI dysfunction was associated with high SOFA score, hypo-albuminemia, catecholamine use, and prolonged length of stay (LOS). GI dysfunction, on the other hand, can cause some complications including inadequate nutrition, and newly developed decubitus ulcers. Conclusion: GI dysfunction should be considered a clinical predictor of inadequate nutrition and prolonged LOS. In addition, the most dramatic risk for GI dysfunction was observed in patients with MDR bacteria growth in the culture and patients in negative fluid balance. Intensivists provide appropriate nutrition for patients, as well as prompt intervention and the development of treatment strategies in the event of GI dysfunction. Keywords: intensive care units, enteral nutrition, water–electrolyte balance, drug resistance, multiple, bacterial, gastrointestinal motility, length of stay